1945
DOI: 10.1103/physrev.68.109
|View full text |Cite
|
Sign up to set email alerts
|

Researches on the Magnetic Deflection of the Hard Component of Cosmic Rays

Abstract: The energy spectrum and positive excess of the hard component of cosmic rays have been investigated both in Rome (50 m above sea level) and at Pian Rosa (3500 m above sea level) by means of a counter system with deflecting magnetized cores. The results of several measurements are discussed, and the following interpretation is suggested: (1) A positive excess of the order of 20 percent is found in the hard component, in agreement with the results of other investigators.(2) The hypothesis of the existence of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

1949
1949
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 25 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…experiments. Bernardini and his collaborators concluded in particular that "a positive excess of the order of 20 percent is found in the hard component, in agreement with the results of other investigators" and that "the hypothesis of the existence of several types of mesons is not confirmed in the lower atmosphere" (see [90], p. 109). In fact, the researches on the positive excess went on for several more years, as they could provide details about the composition of cosmic rays at different heights, and about the production of particles and other interactions which took place within cosmic rays at different altitudes [91][92][93].…”
supporting
confidence: 61%
See 2 more Smart Citations
“…experiments. Bernardini and his collaborators concluded in particular that "a positive excess of the order of 20 percent is found in the hard component, in agreement with the results of other investigators" and that "the hypothesis of the existence of several types of mesons is not confirmed in the lower atmosphere" (see [90], p. 109). In fact, the researches on the positive excess went on for several more years, as they could provide details about the composition of cosmic rays at different heights, and about the production of particles and other interactions which took place within cosmic rays at different altitudes [91][92][93].…”
supporting
confidence: 61%
“…They performed more experiments in the years 1941-1943 and published several papers (see in particular [87,86,88,89]). In an outline of their research work, published in the Physical Review in 1945 [90], they explained that they had investigated the energy spectrum and positive excess of the hard component of cosmic rays for "cogent reasons", as "the positive excess in the meson spectrum is probably connected with the positive nature of the primary radiation" and "a study of the variation of the positive excess with height would probably be interesting and might throw some light on the process of creation of the mesons" (see [90], p. 110). Both in Rome and at Pian Rosà, the Rome physicists had used the same experimental apparatus, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation